Annotated checklist and genetic data for parasitic helminths infecting New Zealand marine invertebrates. Issue 3 (27th July 2022) - Bennett, Jerusha; Poulin, Robert; Presswell, Bronwen
Abstract: Parasitic helminths with complex life cycles require multiple hosts in a particular order to complete their life cycles. Although almost all helminths infect invertebrates at some point in their life cycle, we know very little about which species of invertebrates harbor parasites compared with what is known for vertebrates. In New Zealand, <1% of marine invertebrates that may be expected to host parasites have records of parasite infections. This is a strong indication that our knowledge of invertebrate parasites within marine ecosystems is highly limited. Here, we provide the first comprehensive parasite–host checklist including data from the literature and newly discovered infections of parasitic helminths infecting marine invertebrates in New Zealand. Including both pre‐existing and newly found data from our survey, we present data on 73 parasite taxa (five acanthocephalans, 13 cestodes, nine nematodes, and 46 trematodes) infecting 62 marine invertebrate species in New Zealand. In addition, we compile existing and new genetic data for many of these parasites, as a useful tool for future studies of parasite biodiversity and phylogenetics.